TEORI BEHAVIORIS-STRUKTURALIS DAN PENERAPANNYA DALAM PEMBELAJARAN BAHASA ARAB - Ainiy, Nurul; Maisaroh, Siti; Akbar, Muhammad Salim (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2022)
Behaviorist-Structural theory is one of the important theories in language learning. This theory is a meeting between behavioral theory in psychology and structuralist theory in linguistics. The combination of these two theories not only creates new principles and views, but also has an impact on the development of language learning, especially second languages. This study aims to describe the behavioralist-structural theory view and its application in Arabic learning. This research is a conceptual study using descriptive-qualitative method. The results of the study show that several learning models that can be applied based on the Behaviorist-Structuralist view are: 1) Repetition of speech and conversation in Arabic, 2) Practice repeating speech with replaced isim/fi'il, 3) Practice expanding sentences patterns, and 4) Exercises for manipulation of isim/fi'il sentences. According to the behavioralist-structuralist view, the teacher and the environment play a major role in the success of learning Arabic as a second language, both in the formal (school) and informal environment (home/family).